Common Pathways in Health Benefit Properties of RSV in Cardiovascular Diseases, Cancers and Degenerative Pathologies - Aires, Virginie; Delmas, Dominique (Current Pharmaceutical Biotechnology, 2015)
Lots of epidemiological studies have put forward the beneficial effects of dietary polyphenols consumption in the prevention of diseases related to aging i.e vascular pathologies, neurodegeneration, cancers and associated inflammatory processes. Among polyphenols, resveratrol (trans-3,4’,5- trihydroxystilbene, RSV), a naturally occurring stilbene widely distributed in foodstuffs such as grapes and wine, has been the most studied. Researches performed since the last decades in vitro, in animal models and in (pre)clinical studies have pointed out its pleiotropic health benefits by acting on multiple signaling pathways which go beyond its originally described direct antioxidant activity. However, its low bioavailability upon oral ingestion and lack of specificity may hamper the translation of the encouraging experimental data into human health benefits. Herein we provide an overview on the capacity of RSV to regulate oxidative stress-induced signaling and to modulate key components of signal transduction pathways which are commonly altered in cardiovascular, neurodegenerative and cancer pathologies. We also have attempted to provide a comprehensive outlook on RSV metabolism and biological activity of its main metabolites and discussed about the new strategies developed to circumvent its poor bioavailability and to improve its therapeutic efficacy, including synthesis of new derivatives and new formulations for its cell delivery.
Keywords: polyphenols